THE RELEVANCE OF JÜRGEN HABERMAS’S THEORY OF COMMUNICATIVE ACTION AS THE PHILOSOPHICAL FOUNDATION OF HUMAN RIGHTS ENFORCEMENT IN INDONESIA - Muklis Al'anam; Radian Salman (Faculty of Law, Universitas Gadjah Mada, 2024)
Abstract Habermas’s theory of communicative action is highly relevant as a philosophical foundation for upholding human rights, emphasizing the intrinsic value of each individual, which must not be eliminated by any power. This is supported by Article 6 paragraph (1) of the International Covenant on Civil and Political Rights, ratified as Law Number 12 of 2005. Critical theory, a school of philosophy, focuses on liberating human knowledge from transcendental and empirical oppression, critiquing ideologies that perpetuate social oppression. Human rights have become a dynamic issue in Indonesia, especially during the Presidential Election, with widespread discussions at national and international levels. Countries, organizations, and individuals are increasingly voicing concerns about human rights issues. These problems are complex, particularly in resolving and sanctioning perpetrators, leading some to view human rights as “merely theoretical.” Applying critical theory is crucial in this context, as perfected by Jürgen Habermas. This research employs normative methods, including statutory, conceptual, and case approaches. It concludes that Jürgen Habermas’s theory of communicative action and John Locke’s natural law are similar, emphasizing the inherent meaning of external rights. This grounding makes Habermas’s theory important for upholding law and human rights internationally, although its implementation remains ambiguous. Abstrak Teori kritis tindakan komunikatif Habermas sangat relevan sebagai fondasi filosofis penegakan HAM yang menekankan nilai intrinsik setiap individu, yang tidak boleh dihilangkan oleh kekuasaan mana pun, sesuai dengan Pasal 6 ayat (1) International Covenant on Civil and Political Rights yang diratifikasi menjadi Undang-Undang Nomor 12 Tahun 2005. Teori kritis adalah aliran filsafat tentang pembebasan pengetahuan manusia dari segala bentuk penindasan transendental dan empiris. Ide teori kritis adalah kritik terhadap ideologi yang bertujuanmenyadarkan manusia akan penindasan sosial dan mencoba membebaskannya. Isu HAM menjadi perbincangan dinamis di Indonesia, terutama pada saat pemilihan presiden, serta di dunia internasional. Berbagai negara, organisasi, dan individu menyuarakan sudut pandang HAM yang ada. Problematika HAM sulit diselesaikan dan penerapan sanksi bagi pelaku sering dianggap “teorik belaka.” Penerapan teori tindakan komunikatif ini penting terkait HAM karena disempurnakan oleh Jürgen Habermas. Penelitian ini menggunakan metode penelitian normatif dengan pendekatan perundang-undangan, konseptual, dan kasus. Hasil penelitian menunjukkan adanya kesamaan konsep antara teori kritis Jürgen Habermas dan aliran hukum kodrat John Locke, yang menekankan hak-hak lahiriah. Teori Jürgen Habermas menjadi penting untuk penegakan hukum dan HAM di dunia internasional, meskipun penerapannya masih ambigu.